Sensors Application Of Digital Signal Processing - Ab Hadi, Nik Azran; Abdullah, Mohd Firdaus; Hashim, Nik Mohd Zarifie; Mohd Saad, Norhashimah; Salleh, Azahari; Ja’afar, A. S. (IJARET, 2015)
Many people claim that current technology causing pollution and destroyed nature.However there are a lot of advantage that occur after the rising of the technology. Digital signal processing is example of the famous rising technology nowadays.This paper is about current sensors that can be use in digital signal processing also to find out how can sensors giving so much advantages in human life.To find out how each sensors work in different ways and also to find out why are so many sensor created.The scope of this article only explain about the uses of sensors,type of sensors,and how the sensors works.To make this articles interesting and informative for the readers with multiple information,it’s have been categorizes according to their characteristic for every sensors.On the other hand to give effective information to readers about nowadays technology especially sensor in digital signal processing.